Central European Elements in the Central Adriatic and its Hinterland in the Early Bronze Age – a Recapitulation (Archaeologia Adriatica, 2025)
Research has shown a complementary image of three main elements as indications of contacts between the region of the central Adriatic and its hinterland with the cultures of the Early Bronze Age in Central Europe. They encompass the settlement material culture (Litzen pottery), military equipment or weapons (solid-hilted daggers), and attire (pins with an eyelet). On the basis of their typological analysis and distribution, which showed that they overlap each other spatially and temporally in certain segments, it can be concluded that within the framework of the Posuška/Posušje or Dinaric group, they are indicators of one and the same cultural and possibly migratory event occurring during the Early Bronze Age.